VISCERAL ADIPOSITY INDEX: A SIMPLE TOOL FOR ASSESSING RISK OF TYPE 2 DIABETES MELLITUS - Zar, Adnan; Ali, Sobia Sabir (Journal of Ayub Medical College Abbottabad, 2022)
Background: The prevalence of type 2 diabetes mellitus (T2DM) has increased recently in Pakistan. Visceral adiposity index (VAI) appears to be a better predictor for metabolic syndrome associated with insulin resistance. VAI has been shown to be linearly and positively associated with diabetes mellitus (DM) in many populations. It is, however, uncertain whether VAI could be associated with T2DM in the Pakistani adult population. Methods: This is a cross-sectional study of 300 outpatients with a newly diagnosed T2DM. Subjects were recruited from Lady Reading Hospital, Pakistan, during the period from April, 2020 to January, 2021. For all study subjects, anthropometric measurements were performed. Blood samples were collected for the assessment of high-density lipoproteins (HDL-C), triglycerides (TGs), glycated hemoglobin (HbA1c), and random blood glucose. Results: Participants with high VAI showed poor glycemic control. The number of patients with poor glycemic control increased across the VAI quartiles. VAI showed significant correlations with TGs (r=0.715, p=<0.001), total cholesterol (TC) (r=0.256, p=<0.001), low density lipoprotein (LDL-C) (r=0.154, p=0.007), uric acid (r=0.205, p=0.019), duration of diabetes (r=0.171, p=0.033), TSH (r=0.163, p=0.007), and random blood glucose (r=0.195, p=0.019). Conclusion: Our data suggest that VAI is significantly and positively correlated with the risk factors of DM such as random blood glucose, uric acid and TSH. The findings of the study do not imply a significant direct association between VAI and DM among the Pakistani adult population. Prospective-large scale studies can help inform an effectiveness of VAI for the prediction of the risk of T2DM among Pakistani population.